Grey water treatment by constructed wetland - ABHIJEET HINDURAO SURVE; Er. Rema K. P (Guide) (Tavanur 2007 Kelappaji College of Agricultural Engineering and Technology)
Grey water treatment by constructed wetland. pollution of water bodies can result in the death of aquatic animals, enhanced growth of aquatic plants which causes meandering of flow and floods. waste water mosquito dengue chikkenguniya ....
Grey water treatment by constructed wetland